Investigation on Sound Absorption Function and Mechanical Behavior of Polycarbonate/Nanosilica-based Nanocomposites. Issue 5 (24th March 2018) - Naderzadeh, Mahdiyeh; Monazzam, Mohammad Reza; Ghasemi, Ismaeil; Arabalibeik, Hossein
ABSTRACT: The present study reports the morphological, mechanical, and sound absorption properties of polycarbonate-based nanocomposites containing nanosilica (0.3 and 0.6 wt%). To this end, the specimens were prepared by melt mixing in a twin-screw extruder. The scanning electron microscopy was also used to ensure the well distribution of nanosilica in the polymeric matrix. The mechanical properties were investigated by tensile, flexural strength, Izod impact, and hardness tests. At the end, sound absorption coefficient of the specimens was checked by standing wave sound impedance tube method in the frequency range of 250–6, 300 Hz. The results showed that only a small amount of nanosilica could improve the mechanical properties of specimens. However, the sound absorption function of specimens had a gradual improvement by increasing nanosilica content. Tensile modulus and strength at yield of the nanocomposite specimens were higher than that of the neat polycarbonate. On the contrary, a decrease in elongation at break was reported, which was attributed to the reduced mobility of the polymer chains due to the presence of nanoparticles. The same behavior was observed in the test results of Izod impact strength of nanocomposites so that adding nanosilica with the wt% of 0.6 to the neat polycarbonate, the impact strength improved by only 5.3%. According to the findings, polycarbonate composites with 0.3 wt% nano-silica, in addition to strengthening the mechanical properties (tensile modulus, flexural strength, and stiffness), could improve the acoustic characteristics of the specimens in low and mid frequencies. The findings also revealed that the performance of pure polycarbonate and 6 wt% nanosilica polycarbonate in upper frequency range was higher and approximately the same as that for 3 wt% nanosilica polycarbonate. GRAPHICAL ABSTRACT: